Strategic Leadership in Action: Unpacking the Alignment Between Strategic Behavior and Strategy at Combipar - Michael H Hadylaya; Anggara Wisesa; Madju Yuni Ros Bangun (Eduvest - Journal of Universal Studies, 2025)
This study explores the influence of leadership behavior on strategic behavior at PT Combined Imperial Pharmaceutical (Combiphar) under the leadership of Michael Haryono Wanandi. The study analyzes how strategic leadership contributed to Combiphar’s transformation from a pharmaceutical company to a consumer health company. Using a mixed-method approach, this study combines qualitative interviews with key executives and a quantitative survey of senior managers. The results of the analysis show that Combiphar’s strategic leadership consists of five key components, which form the SAVEE model: Strategic Planning, Adaptive Capability, Visionary Leadership, Empowerment & Collaboration, and Ethical Leadership. This model is reflected in the company’s strategic behavior, AIM (Enthusiastic and Intelligent in Achieving Results, Integrity, Synergistic & Harmonious Cooperation, Winning the Hearts of Customers). Visionary and Ethical Leadership proved to be key predictors of long-term success, while Strategic Planning, Adaptive Capability, and Empowerment & Collaboration require further strengthening. Key recommendations include validating and integrating the SAVEE model in leadership development, enhancing Visionary and Ethical Leadership programs, optimizing data-driven Strategic Planning, and strengthening Enablement & Collaboration through cross-functional teams and reward systems.